The Value Of Physical Examination In The Diagnosis Of Elbow Fracture In Elbow Trauma In Adult Patients With Positive Clinical Findings (Journal of Pharmaceutical Negative Results, 2023)
Background: The existence of a method to rule out elbow fractures in acute injuries prevents unnecessary radiography, resulting in reduction of costs. Clinical decision tools are widely available and accepted to standardize clinical assessment after limb injury, but currently there is no sensitive predictive method for elbow assessment. Therefore, this study aimed at investigating the value of physical examination in diagnosing elbow fracture in elbow trauma among patients with positive clinical findings.Materials and Methods: This cross-sectional study was conducted on patients with elbow trauma who were referred to an educational center. Then the demographic information questionnaire including age, sex and injury mechanism was completed by the researcher. Elbow examinations, including observation and touching, were performed for all patients, and tenderness point tests and extension tests were performed for all patients. In addition, anteroposterior and lateral radiographs of the elbow were performed for all patients. Visual pain questionnaire was completed for all patients.Results: A total of 150 patients were included in the study. The patients consisted of (74.83%) men and (25.17%) women. In terms of fractures detected in elbow radiography, 41 patients showed fractures in the elbow joint and 106 patients (72.11%) did not have fractures. The sensitivity and specificity of severe pain (19.51% and 82.08%), swelling (26.83% and 62.26%), deformity (31.71% and 100%), ecchymosis (56.1% and 87.74%), abnormal range of motion (100% and 83.02), extension test (97.56% and 94.34%), flexion test (90.24% and 58.49%), pronation test (26.83% and 80.19%), supination test (41.46% and 93.4%) and point test (100% and 66.98%) was calculated.Conclusion: The extension test demonstrated the highest accuracy for the diagnosis of elbow fracture, while the local swelling has the lowest accuracy for this diagnosis. Point tenderness and abnormal range of motion had the highest sensitivity, and deformity had the highest specificity for elbow fractures.